Genetic relationship between coptotermes gestroi and coptotermes vastator (Isoptera: Rhinotermitidae) - Beng Keok Yeap (2018)
The phylogenetic relationship of Coptotermes gestroi (Wasmann) and Captotermes vastator Light (Isoptera: Rhinotermitidae) was determined using DNA sequence comparisons of mitochondrial genes. Partial sequences of the ribosomal RNA small subunit 12S, ribosomal RNA large subunit 16S, and mitochondrial COII were obtained from nine populations of C. gestroi from South East Asia (Malaysia, Singapore, Thailand, and Indonesia) and four populations of C. vastator from the Philippines and Hawaii. In addition, four populations of Coptotermes formosanus Shiraki and Globitermes sulphureus (Haviland) were used as the outgroups. Consensus sequences were obtained and aligned. C. vastator and C. gestroi are synonymous, based on high sequence homology across the 12S, 16S, and COII genes. The interspecific pairwise sequence divergence, based on Kimura 2-parameter model between C. gestroi and C. vastator, varied only up to 0.80%. Morphometric measurements of 16 characteristics revealed numerous overlaps between the examined individuals of both species. Based on the molecular phylogenetics and morphometric data, it is proposed that C. vastator is a junior synonym of C. gestroi. © 2007 Entomological Society of America.